The influence of stress, optimism, and music training on music uses and preferences. (January 2014) - Getz, Laura M.; Marks, Stephen; Roy, Michael
In the present study we examined how different aspects of a person's life, such as the amount of stress experienced, levels of optimism, and the amount of musical training received, were related to their motives for listening to music (for emotional regulation and/or for cognitive stimulation) and their preferences for what types of music to listen to. Participants ( N = 154) completed surveys measuring stress, optimism, music uses, and music preferences. Results indicate that high stress ratings predicted the use of music for emotional regulation. Additionally, optimistic individuals also tended to use music emotionally, meaning that stress and optimism, though highly negatively correlated, appear to influence uses of music independently. People with more music training followed a different pattern; even though they had higher stress ratings and lower optimism ratings overall, individuals with music training tended to listen to music for cognitive reasons more than for emotional regulation. These findings help us further understand the variables that lead to individual differences in music uses and preferences.